O-009 Cone beam CT of cerebrovascular stents. (16th November 2010) - Gounis, M; Patel, N; Norbash, A; Lee, S; Noordhoek, N; Blijd, J; Babic, D; Wakhloo, A
Abstract : Purpose: To develop, optimize and assess the clinical performance of a method for visualizing intracranial stents and their relationships to the host vasculature. Materials and methods: Cone beam CT (CBCT) was performed using a flat panel detector angiography system. Datasets were reconstructed from 620 projection images acquired over a 200° arc (rotation time 20.7 s) at 80 kVp and a total of 260 mAs. To maximize spatial resolution, projection images were obtained using a small detector format (22 cm) and reconstructions were performed without pixel binning. A contrast injection protocol was optimized in a porcine model for balance between stent visualization host vessel opacification. Three different intracranial stents were deployed in the internal maxillary arteries of two Yorkshire swine. Selective CBCT angiography was performed at contrast concentrations between 10 and 30% (Iopamidol 51%, by volume in normal saline) and flow rates between 0.5 and 3.5 ml/s. The CBCT datasets were reviewed and the optimal combination of parameters was used for clinical testing. The clinical study was approved by our institutional review board. 57 CBCT examinations of implanted neurovascular stents were performed in 55 patients undergoing cerebral angiography. Two patients each received stents in two locations during treatments of separate aneurysms. Five cases were excluded from the study: four due to the use of balloon mounted stents that are visible with standard angiography and one due to failed contrast injection. The majority of included cases (46/52) were stents placed for treatment of intracranial aneurysms. Stents were placed in six cases to treat dissecting vertebral artery aneurysm, vertebrobasilar insufficiency, acute ischemic stroke and severe middle cerebral artery stenosis. For clinical evaluation, the CBCT dataset was reconstructed with a 512 3 matrix covering a cubic FOV of 34.4 mm in each dimension (67 μm isotropic voxels). Images were assessed through blinded review by three interventional neuroradiologists using a structured questionnaire. Stent and host vessel visibility were rated on scales of 1–3, and the ability to assess stent apposition was rated 'yes' or 'no'. Results: The optimal injection protocol for carotid artery injections was 20% contrast at a flow rate of 3.0 ml/s. The flow rate was reduced to 2.0 ml/s for clinical vertebral artery injections. In 96.1% of cases (50/52), all reviewers rated visualization as sufficient to delineate the configuration and position of each stent (score≥2). In 100% of these cases, all reviewers agreed that the studies were sufficient to evaluate stent apposition to the vessel wall. Statistical agreement on the scoring of stent visualization in all cases was strong (ICC=0.67). In 15 cases, CBCT identified important findings that could not be well delineated on conventional angiography or multidetector CT. These included: the relationship between a stent, a coil mass and important vessels originating in close proximity to an aneurysm, stent thrombosis, neointimal hyperplasia, stent malapposition and calcified atheroma underlying a stent. Conclusion: CBCT is a reliable technique that provides good quality visualization of intracranial stents and their host vessels, enabling neuroradiologists to identify important findings that are not seen using standard methods.